Numerical study of HCl and SO2 impact on sodium emissions in pulverized-coal flames. (15th August 2019) - Wan, Kaidi; Wang, Zhihua; Xia, Jun; Vervisch, Luc; Domingo, Pascale; Lv, Yu; Liu, Yingzu; He, Yong; Cen, Kefa
Graphical abstract: Highlights: The coupled response of coal oxidation and sodium reactions is studied. Sodium species are scrutinized in both one- and two-dimensional flames. Na, NaOH and NaCl drive the sodium chemical paths in coal flames. HCl has a much stronger ability to react with sodium species than SO2 . Abstract: Sodium emissions during pulverized-coal combustion (PCC) are known to result in severe ash-related operating issues of coal furnaces, e.g., fouling, slagging and corrosion. To relieve these issues and advance the clean utilization technologies of coal, a better understanding of the fundamental mechanisms driving the formation and transformation of the sodium species is required. In the present study, sodium emissions have been simulated in both one-dimensional (1D) premixed/diffusion flames of the coal volatile and an early-stage two-dimensional (2D) pulverized-coal flame. The properties of Loy Yang brown coal are used. The DRM22 skeletal mechanism is employed for volatile-gas combustion, and the reaction of sodium species is modeled by a detailed mechanism encompassing the elements Na, C, H, O, S and Cl. The compositions of the volatile fuels are obtained from the chemical percolation devolatilization (CPD) model, including CH4, C2 H2, CO, H2, CO2 and H2 O. The initial species of Na, Cl and S in the volatile gas is set to be NaOH, HCl and SO2, respectively. The transformation characteristics of 12 sodium species are investigated in both the 1D volatile flames and the 2D pulverized-coal flame. The response of the sodium chemistry to volatile-gas combustion is analyzed under fuel-lean, stoichiometric and fuel-rich conditions. Na, NaOH and NaCl are found to be the major sodium species during the combustion. Parametric studies with HCl, SO2 or both species removed from the volatile are then performed to investigate their effects on the sodium transformation characteristics in both the 1D and 2D flames. The results show that HCl has a much stronger ability to react with sodium species than SO2 .